The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/s0004-2803.202301000-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pharmacist Counseling on Patient Medication Compliance and Helicobacter Pylori Eradication Among Jordanian Outpatients

Abstract: Background: To examine the impact of pharmacist counseling and follow-up on patient’s medication compliance and Helicobacter Pylori (H. pylori) eradication and evaluate the efficiency of an eradication regimen consisting of Clarithromycin 500 mg, Amoxicillin 1 g, and Lansoprazole 30 mg, twice daily for 14 days. Methods: Two hundred patients undergoing endoscopy and positive rapid urease tests were included in the present study. Patients were randomly divided into two groups: an intervention group (n=100) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Kotilea et al demonstrated that eradication was achieved in 89.9% of children with high compliance, but in only 36.8% of children with low adherence ( Kotilea et al, 2017 ). In another study, counseling by pharmacists increased medication adherence from 27.5% to 45%, with the eradication rate of H. pylori increasing from 28.5% to 42.5% ( Shoiab et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kotilea et al demonstrated that eradication was achieved in 89.9% of children with high compliance, but in only 36.8% of children with low adherence ( Kotilea et al, 2017 ). In another study, counseling by pharmacists increased medication adherence from 27.5% to 45%, with the eradication rate of H. pylori increasing from 28.5% to 42.5% ( Shoiab et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%